Applications of the inverse theta number in stable set problems - Ujvári Miklós (Acta cybernetica, 2014)
In the paper we introduce a semidefinite upper bound on the square of the stability number of a graph, the inverse theta number, which is proved to be multiplicative with respect to the strong graph product, hence to be an upper bound for the square of the Shannon capacity of the graph. We also describe a heuristic algorithm for the stable set problem based on semidefinite programming, Cholesky factorization, and eigenvector computation.